Study on the antioxidant and antitumoral activity of propolis - del Río del Rosal, Elisa; Casas Arrojo, Virginia; Gómez Turpín, Eva M.; Gil Gómez, José; Abdala Díaz, Roberto; Figueroa, Félix L. (Ars Pharmaceutica (Internet), 2017)
Introduction: Propolis is the substance that protects the hive, a resin of complex and viscous composition bees use in the repair and protection of the hive. The material from which propolis arises are the resins, shoots and petioles of the leaves of different plants, so it has a very complex chemical composition that varies depending on the flora of the bees collection. It offers an antimicrobial, anti-inflammatory capacity related to its antioxidant, immunomodulatory power, among others. Aims: In this work, antioxidant and antitumoral activities of different propolis collected from different areas of the province of Malaga, comparing them with one from the Bohemian region to the south of the Czech Republic are studied. Material and methods: Antioxidant activity was determined according to the ABTS+/S2O8K2 method. In addition, the quantity of total proteins from the nitrogen content and subsequently the cytotoxicity and antitumoral activity of the propolis of Puerto de la Torre, north of Malaga, are measured according to the 3-(4,5-dimetiltiazol-2-il)-2,5-diphenyl tetrazolium bromide method. Results: It was observed that propolis has high antioxidant activity, although it has a lower amount of proteins. Propolis has high toxicity and higher antitumoral activity against colon cancer than leukemia. Discussion: With all these data, it can be concluded that propolis offers different activities of interest, for the food and cosmetic industry, among which the high antioxidant and antitumoral capacity.